Transition metal catalyzed synthesis of glycoclusters from sugar alkynes. - Trono, Corazon. (University of Ottawa (Canada), 2001)
A series of rigid neoglycoclusters and dimers were synthesized from sugar alkynes using Sonogashira coupling. Rigid dimers consisting of two mannoside or galactoside derivatives tethered to a phenylacetylene core were constructed. By oxidative coupling of glycosidic terminal acetylenes, rigid dimers consisting of two mannoside residues tethered to a diphenyl-di-acetylene core were synthesized. Utilizing the ortho-, meta- and para-acetylene substituted phenyls, rigid dimers having monosaccharide units oriented at 60°, 120° and 180° with each other were generated. Convergent synthesis of glycosidic clusters emanating from a benzene core was attained utilizing Co2(CO)8 catalyzed cyclotrimerization of acetylenes disubstituted with monosaccharide residues. Trimers and hexamers, including a hexameric "molecular asterisk" were constructed. Galactoside and mannoside clusters were synthesized. Semi-rigid dimers were also synthesized by O-glycosidation of dihydroxybenzene and 2-butyn-1,4-diol. Preliminary binding studies of the mannoside dimers, trimer and hexamers revealed that the hexamer and rigid dimers having two phenyl-acetylenes at the core have promising activity vs. the phytohemagglutinin from Canavalia ensiformis (ConA.). Optimum binding with ConA was demonstrated by the para-disubstituted di-phenyl-diacetylene and the molecular asterisk. These two compounds showed comparable activities giving an indication of the minimum binding requirements of mannosaccharide conjugates with Concanavalin A.
Keywords: Chemistry, Organic.